Question mark ear deformity-revisited - Al-Qattan, Mohammad M. (Eur J Plast Surg, 2016)
We report on two unusual cases of Cosman (question mark) ear; both required modifications of the standard techniques for surgical correction. The first patient presented with a unilateral question mark ear and concurrent ear prominence and bulging of the cartilage of the anti-helix. Simultaneous correction was done using a combination of cartilage suturing/scoring (for the prominence and the cartilage bulge) as well as Al-Qattan’s “v-y skin flap-cartilage graft-z-plasty” technique (for the correction of the ear cleft deformity). The second patient had aurico-condylar syndrome with bilateral ear deformity and complete separation of ear lobes from the external ear. Staged transposition followed by Al-Qattan’s technique resulted in a satisfactory outcome. Level of evidence: Level V, therapeutic study.